IDENTIFICATION OF GREEN ARCHITECTURAL CHARACTERISTICS OF TENGANAN PEGRINGSINGAN VILLAGE, KARANGASEM, BALI - Aritama, Anak Agung Ngurah; Laskara, Gede Windu; Satria, Made Wina (ASTONJADRO, 2022)
Tenganan Pegringsingan village is one of most Bali Aga villages that located at Karangasem Regency, Bali. This village has a variety of vernacular buildings especially a settlement building. The settlement buildings that is a traditional houses are dwelling that still maintain pattern and shape of the building in the past. In this article will discuss about characteristics of green architecture in vernacular architecture and the genius that applied by people to response the environmental issues. Research using qualitative descriptive method by collecting data through field observations on vernacular building objects followed by a drawing of the object. The result of this research show that there four characteristics of green architecture on vernacular buildings at Tenganan village including aspects of land use, energy efficiency, water conservation, and cycles and material sources.